The concept of social liberalism of Frederick August von Hayek - Wieczorek, Emilia (Kultura-Społeczeństwo-Edukacja, 2021)
According to some criteria, social liberalism is considered to be one of the types of liberalism. These studies are a reflection on Frederick August von Hayek’s concept of social liberalism, who is a supporter of political and economic freedom, but above all, individual freedom. This analysis aims to present the leading ideas of his social philosophy in the area of the function of the state, democracy, freedom, spontaneous order of individualism and equality.